MENTAL HEALTH INTERVENTIONS FOR FIRST RESPONDERS: EVALUATING THE EFFICACY OF TRAUMA-FOCUSED THERAPY - Suyanti; Costa, Tiago; Silva, Pedro (World Psychology, 2026)
First responders are routinely exposed to traumatic events, placing them at high risk for developing mental health disorders such as PTSD, anxiety, and burnout. Despite the critical role these professionals play, mental health interventions remain limited. Trauma-Focused Therapy (TFT) has shown promise in treating trauma-related disorders, yet its efficacy for first responders has not been extensively studied. This research aims to evaluate the effectiveness of TFT in improving the mental health outcomes of first responders, specifically in reducing PTSD, anxiety, depression, and burnout symptoms. The study employed a randomized controlled design, with 120 first responders assigned to either the experimental group receiving TFT or the control group. Pre-, post-, and six-month follow-up assessments were conducted using standardized instruments such as the Clinician-Administered PTSD Scale (CAPS), Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), and Maslach Burnout Inventory (MBI). Results indicated significant reductions in PTSD, anxiety, depression, and burnout scores in the experimental group, with improvements sustained at the six-month follow-up. The control group showed minimal changes. These findings suggest that TFT is an effective intervention for enhancing the mental well-being of first responders. The study highlights the importance of incorporating TFT into mental health support systems for first responders.